(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To study of inflammatory (IL-6) and biochemical markers (Ferritin, CRP and D-Dimer) correlatedwith CT chest severity score[SpO2, RR, PaO2/FiO2] in COVID 19 patients. Methods: A Retrospective, observational study was conducted in Meenakshi Medical College Hospital and Research institute, Kanchipuram, Tamil Nadu. Totally 100 Covid 19 patients were admitted in the Covid ward [IL-6, CRP, D-Dimer and RT PCR swab for COVID 19 positive and radiologically positive] between February 2021 to June 2021. The patient was clinically, radiologically, and biochemically evaluated. Based on the inflammatory, biochemical markers and CT chest severity score was used to differentiate the patients into mild, moderate, and severe groups. The relationship between CT Severity score and Clinical parameters such as SpO2, RR, PaO2/FiO2 and Biochemical markers [Ferritin, CRP, D-Dimer] were studied. Results:IL-6, Biochemical markers like CRP, Ferritin and D- dimer and CT chest severity score was found to be positively correlated with decreased SpO2 levels, decreased PaO2/ FiO2, increased RR level. IL-6, D-Dimer and CRP levels were significantly increased (P < 0.001) in moderate, severe Covid 19 patients when compared with mild and control patients. Conclusion: The 25 CT Severity score scores well with the Clinical parameters and biochemical markers. Our data suggest that inflammatory and biochemical markers significantly correlated with CT Chest Severity Score based on the severity of COVID 19 Patients.